ANEKA TEKNIK STIMULASI DAN APLIKASINYA DALAM MENGEMBANGKAN KREATIVITAS ANAK USIA 5-8 TAHUN - Rosita Wondal (Universitas Khairun, 2015)
Education is verbalistic and mechanistic. Child development covers several aspects they are perceptual-cognitive, social-language, fine motor and gross motor skill. As we know that 5-8 years of age is a stage that is vulnerable to the reduction of creative potential so it is necessery to develop their creativity stimulation technique.Children know and memorize more some words, terms, numbers and symbols. Therefore, knowledge and awareness of parents and teachers needed to provide stimulation to the development of creativity. There are several important reasons such as child’s creativity is a basic skill.